Synthesis of endohedral fullerenes by molecular surgery - Sally Bloodworth; Richard J. Whitby (Communications Chemistry, 2022)
‘Molecular surgery’ is a useful method through which to create endohedral fullerenes that aren’t accessible by conventional physical methods of trapping small atoms and molecules. Here, the authors review the organic chemistry behind molecular surgery, describing the methods to access open-cage intermediates alongside the cage-closing chemistry.